Two genotypes of H3N2 swine influenza viruses identified in pigs from Shandong Province, China - Zhao, Yuzhong; Han, Lebin; Sang, Haotian; Yang, Pingping; Hou, Yanmeng; Xiao, Yihong (Frontiers in Cellular and Infection Microbiology, 2024)
Swine influenza virus (SIV) is a highly contagious pathogen that poses significant economic challenges to the swine industry and carries zoonotic potential, underscoring the need for vigilant surveillance. In this study, we performed a comprehensive genetic and molecular analysis of H3N2 SIV isolates obtained from 372 swine samples collected in Shandong Province, China. Phylogenetic analysis revealed two distinct genotypes. The surface genes of both genotypes clustered with the human-like H3N2 lineage, while the internal genes of one genotype clustered with the 2009 pandemic H1N1 (pdm/09) lineage. In the second genotype, the NS gene clustered with the classical swine (CS) H1N1 lineage, while the remaining internal genes clustered with pdm/09, suggesting stable integration of pdm/09 gene segments into H3N2 SIV. Homology analysis showed over 96% genetic similarity between the isolates and reference strains from China and Brazil, suggesting potential transmission through swine trade or human movement. Molecular characterization identified amino acid substitutions in the HA protein (190D, 226I, and 228S), potentially enhancing the virus’s affinity for human-like receptors, thereby increasing the zoonotic risk. Key mutations in the PB2 (271A, 591R), PA (336M, 356R, 409N), and M2 (S31N) proteins, along with novel drug resistance mutations, indicate the potential for enhanced virulence and drug resistance in these isolates. Moreover, glycosylation site analysis revealed four differences, and antigenic site analysis showed 13 differences between the HA proteins of the isolates and the WHO-recommended vaccine strain A/Cambodia/E0826360/2020 for the 2021–2022 season, which may reduce vaccine efficacy. Serological analysis revealed that 11 out of the tested serum samples were positive for H3N2 antibodies, resulting in an overall positivity rate of 0.42%. These findings emphasize the urgent need for strengthened SIV surveillance in China to monitor the risk of human transmission and ensure better preparedness for future influenza outbreaks.